Analisis Literatur Tentang Penerapan Adaptive Learning Untuk Menyesuaikan Gaya Belajar Siswa Dalam Pembelajaran PAI - Ulfa Maghfirah; Maliana Julia Saputri; Ilmika Raudhatul Jannah; Jasiah, Jasiah (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
Every student has a different learning style, such as visual, auditory, and kinesthetic. These differences influence how they understand and absorb learning material. To address this need, adaptive learning has emerged as a solution that can tailor the learning process to each student’s characteristics. This study aims to examine the implementation of adaptive learning in adjusting instruction to students’ learning styles. The method used is a literature review of various national and international scholarly articles published in the last five years. The findings indicate that adaptive learning can improve students’ understanding of the material, learning outcomes, as well as their motivation and engagement in the learning process. Moreover, adaptive platforms offer greater flexibility and accessibility, allowing students to learn in ways that best suit their individual preferences. These results suggest that adaptive learning is an effective approach for accommodating diverse learning styles and enhancing the quality of education.